Analisis Pengaruh Struktur Modal Terhadap Praktik Manajemen Laba - ines devina; Sandy Harianto; Johan Yanto (Studi Akuntansi dan Keuangan Indonesia, 2019)
The research objective is to analyze the influence of capital structure on earnings management practices. The research using multiple regressions examined 192 non-financial companies listed on Indonesia Stock Exchange from 2005 to 2014 period. The proxies of capital structure are debt-to-equity ratio and debt-to-asset ratio, while earnings management calculated through discretionary accruals from Jones, Modified Jones, cross-sectional industrial models. The results showed that there is a negative significant influence from firm’s capital structure to earnings management (α <0.05). This indicates that higher use of debt would increase the difficulties of debt covenant performance requirements; hence it increases the degree of control over the company, leaving less opportunity for earnings management.